Root growth inhibition and ultrastructural changes in radish root tips after treatment with aqueous extracts of Fallopia japonica and F. ×bohemica rhizomes. - Šoln, Katarina; Žnidaršič, Nada; Dolenc Koce, Jasna (Protoplasma, 2022)
Allelopathic compounds released by invasive alien plants can suppress the growth of plants in their vicinity. The aim of this study was to investigate changes in tissue and cell structure in roots of radish seedlings treated with 10% aqueous extracts of rhizomes from the invasive knotweeds Fallopia japonica and F. ×bohemica. After 7 days of growth without and with aqueous extracts from these rhizomes, the anatomical and ultrastructural changes in the radish seedling roots were analyzed with light and transmission electron microscopy, and hydrogen peroxide was localized with diaminobenzidine, to define oxidative stress. The roots of radish seedlings treated with the knotweed extracts were shorter and thicker, due to the shorter and wider shapes of their cortex cells, which were organized in more columns than the control roots. There were signs of cell damage and oxidative stress in the root cap cells, and to a lesser extent in the meristematic zone. As well as the irregularly shaped nuclei and plasma membrane detached from the cell wall, the most prominent ultrastructural effects in the root cap cells of these aqueous rhizome extracts were the ring-shaped form of the mitochondria and large endoplasmic reticulum bodies. Excessive vacuolization was seen for the cells of the root apical meristem.